5(y+2)=18-1+3y

Simple and best practice solution for 5(y+2)=18-1+3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+2)=18-1+3y equation:


Simplifying
5(y + 2) = 18 + -1 + 3y

Reorder the terms:
5(2 + y) = 18 + -1 + 3y
(2 * 5 + y * 5) = 18 + -1 + 3y
(10 + 5y) = 18 + -1 + 3y

Combine like terms: 18 + -1 = 17
10 + 5y = 17 + 3y

Solving
10 + 5y = 17 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
10 + 5y + -3y = 17 + 3y + -3y

Combine like terms: 5y + -3y = 2y
10 + 2y = 17 + 3y + -3y

Combine like terms: 3y + -3y = 0
10 + 2y = 17 + 0
10 + 2y = 17

Add '-10' to each side of the equation.
10 + -10 + 2y = 17 + -10

Combine like terms: 10 + -10 = 0
0 + 2y = 17 + -10
2y = 17 + -10

Combine like terms: 17 + -10 = 7
2y = 7

Divide each side by '2'.
y = 3.5

Simplifying
y = 3.5

See similar equations:

| 6/7x-4 | | 2(x+8)=x-19 | | 2x+4y-(6+3z)=2y-3z+2 | | 19+7=9 | | 29-c=15 | | x+26=79 | | -9m+3-2m+1= | | 63*y^3/35*y^5 | | 2x+27=8x | | (1/5)(x-25)=(4/5) | | 3--1= | | 0=-16t^2+32t+20 | | Y-64=-7/2 | | 2(5z-3)-2(3-2z)=6 | | 5.7x-4=4.7x | | 5c=175 | | 2x^2+20x-7=0 | | 2(4z-3)-2(2-3z)=6 | | c-35=78 | | -7-3x+4x=14 | | (4x)=(x+90) | | 25u^3+105u^2-100u=0 | | 7.5(x-2)=-0.5x+33 | | 3.5/6.6=x | | (-a+4)-(2a-3)= | | .8x-2.4=.8 | | 6x-9+(6x+3)=180 | | 8x+2=-6+6x+20 | | 2x-5x-10=-3x+9-10 | | 5k+7=k+4 | | 5x-2=5(x+7) | | 16+8x=72 |

Equations solver categories